The Excellence Plus for Government Public Relations in the New Media Era - Kriyantono, Rachmat; Safitri, Reza (Institut Komunikasi dan Bisnis LSPR, 2024)
ABSTRACT The paper aims to offer ideas on the use of the Excellent Plus Model to strengthen government public relations functions in the new media era. This model contributes to developing the practice of Government Public Relations so that it can carry out its function as the person in charge of the institution's communication system in supporting public services in the new media era. This model was developed through an effort to review the literature, which found that there are still gaps and unsynchronized between scientific perspectives, regulations, and public relations applications that raise issues of structure, role, purpose, and ethics. The Excellence Plus model offers a solution because it combines the universal dimensions of public relations practice and the local character of community communication. This model has the advantage of being workable because it is derived from the dominant theory in Public Relations and is universal in various types of organizations, with a way of application that adapts to the unique character of the organization. The challenge in applying this model is the great difficulty in changing perceptions about the PR function, synchronizing various government regulations, institutional restructuring related to nomenclature, and preparing human resources. Keywords: communication; excellence plus; local character; new media; public relations